2010
DOI: 10.1177/0269215510380830
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preoperative exercise therapy on postoperative outcome: a systematic review

Abstract: Preoperative exercise therapy can be effective for reducing postoperative complication rates and length of hospital stay after cardiac or abdominal surgery. More research on the utility of preoperative exercise therapy and its long-term effects is needed as well as insight in the benefits of using risk models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
218
1
20

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(249 citation statements)
references
References 60 publications
10
218
1
20
Order By: Relevance
“…Conversely, it can be presumed that a preoperative hospital stay has several effects on the patient. Firstly, it has been shown that preoperative mobility decreases the risk of postoperative complications [29][30][31]. Secondly, a longer Similarly with the current study, some data has shown that hypertension is an independent risk factor for developing SSI.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Conversely, it can be presumed that a preoperative hospital stay has several effects on the patient. Firstly, it has been shown that preoperative mobility decreases the risk of postoperative complications [29][30][31]. Secondly, a longer Similarly with the current study, some data has shown that hypertension is an independent risk factor for developing SSI.…”
Section: Discussionsupporting
confidence: 74%
“…The risk factors with continuous scales were dichotomized for statistical purposes. The BMI abnormality original classification included underweight (< 18.5), overweight (25)(26)(27)(28)(29)(30), class I obese (30)(31)(32)(33)(34)(35), class II obese (35)(36)(37)(38)(39)(40) and class III obese (> 40) groups as per pre-defined NSQIP BMI ranges. The altered classification classified BMI levels below 18.5 and above 25 as abnormal (under/overweight) and those between 18.5 and 25 as normal [27].…”
Section: Risk Factorsmentioning
confidence: 99%
“…For radiculopathy patients, PT prior to surgery, in general, has been associated with beneficial effects on postoperative patient outcomes. [19][20][21][22][23][24] In the current study, the difference in baseline functioning, age, and smoking history between those patients receiving PT and those who did not could account for some of the postoperative differences observed. These factors could influence surgical outcomes independently of the use of PT.…”
Section: Discussionmentioning
confidence: 99%
“…Эффекты такого вида преабилитации прояви-лись и в сокращении сроков пребывания пациен-тов в послеоперационном периоде в отделении реанимации, а также общего времени госпита-лизации [42,43]. Рандомизированное исследо-вание Arthur H.M. с соавторами [42] показало, что пациенты, занимавшиеся физическими тре-нировками два раза в неделю в период подготов-ки к КШ, провели меньше времени в отделении интенсивной терапии и в стационаре в целом в послеоперационном периоде.…”
Section: аналитические обзорыunclassified